NEW SPECIES OF CATANTHERA AND MEDINILLA (MELASTOMATACEAE) FROM HALMAHERA, INDONESIA AND A NEW NAME FOR A MEDINILLA FROM MADAGASCAR - Abdulrokhman Kartonegoro; J. F. Veldkamp (BRIN Publishing (Penerbit BRIN), 2017)
VELDKAMP, J. F. & KARTONEGORO, A. 2017. New species of Catanthera and Medinilla (Melastomataceae) from Halmahera, Indonesia and a new name for a Medinilla from Madagascar. Reinwardtia 16(1): 25 - 30. - One new species of Catanthera and four of Medinilla (Melastomataceae) from Halmahera, Moluccas, Indonesia, are described. One also occurs in Morotai. A new name was needed for M. intermedia H. Perrier (1932), non Blume (1831), from Madagascar.